Decompensated cirrhosis may be a risk factor for adverse events in endoscopic retrograde cholangiopancreatography. (24th March 2016) - Inamdar, Sumant; Berzin, Tyler M.; Berkowitz, Joshua; Sejpal, Divyesh V.; Sawhney, Mandeep S.; Chutanni, Ram; Pleskow, Douglas K.; Trindade, Arvind J.
Abstract: Background and Aims: There are limited data regarding the safety of endoscopic retrograde cholangiopancreatography (ERCP) in cirrhosis. The current literature consists of small series totalling less than 225 patients. Methods: Retrospective matched cohort study of the National Inpatient Sample (NIS) for 2009. We compared adverse events of cirrhotic patients who underwent ERCP ( n = 1930) with a matched control group that consisted of randomly selected non‐cirrhotic patients who underwent ERCP ( n = 5790). An additional control group, to measure cirrhosis‐related adverse events, consisted of cirrhotic patients undergoing non‐pancreaticobiliary endoscopy. Results: ERCP‐associated adverse events of post‐ERCP pancreatitis (PEP) (8.3% vs. 5.5%) and bleeding (2.3% vs. 1.0%) were more common in the cirrhosis cohort vs. the non‐cirrhosis cohort (all P < 0.05). In subgroup analysis, compensated cirrhotic patients ( n = 1308) had a similar adverse event profile to non‐cirrhotic controls except for a slightly higher rate of PEP (7.7% vs. 5.5%; P < 0.05). However, decompensated cirrhotic patients ( n = 622) had statistically significant higher rates of PEP (9.7% vs. 5.5%) and bleeding (4.3% vs. 1.0%), compared with non‐cirrhotic controls respectively ( P < 0.05). In regard to cirrhosis‐related adverse events, cirrhotic patients undergoing ERCP were more likely to develop bacterial peritonitis vs. cirrhotic patients undergoing non‐pancreaticobiliary endoscopy (2.2% vs. 1.1%; P < 0.005). Conclusion: ERCP adverse events were statistically higher among patients with decompensated cirrhosis. This increased risk needs to be confirmed with prospective studies. A thorough risk/benefit assessment should be performed prior to performing ERCP in decompensated cirrhotic patients.